2019
DOI: 10.1021/acssuschemeng.9b01479
|View full text |Cite
|
Sign up to set email alerts
|

Sb(V) Reduced to Sb(III) and More Easily Adsorbed in the Form of Sb(OH)3 by Microbial Extracellular Polymeric Substances and Core–Shell Magnetic Nanocomposites

Abstract: Antimony (Sb) is a priority pollutant. Reduction adsorption is an effective treatment, because Sb(III) is easier to remove than Sb(V). However, it is unclear what specific ionic form is prone to be adsorbed. In this study, microbial extracellular polymeric substances (EPS) and magnetic nanocomposite EPS@Fe 3 O 4 were first used in the simultaneous reduction and adsorption of Sb(V). The relevance between adsorbent and ionic forms was investigated. EPS achieved high Sb adsorption capacity (120 mg/g) and EPS@Fe 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…High affinity of antimonite to O-bearing groups of microbial extracellular polymeric substances and solid model peat NOM has just recently been shown. 37,72 Although Sb−C distances proposed by Besold et al 37 were slightly longer (2.90 Å) than the fitted Sb−C distance of our best-fit reference compound "Sb(III) complexed with Aldrich humic acid" (2.83 Å, Figure SI-8, Table SI-20), both reside in the range of published Sb−C distances of ∼2.85 -∼ 2.92 Å, 73,74 indicative for phenol groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…High affinity of antimonite to O-bearing groups of microbial extracellular polymeric substances and solid model peat NOM has just recently been shown. 37,72 Although Sb−C distances proposed by Besold et al 37 were slightly longer (2.90 Å) than the fitted Sb−C distance of our best-fit reference compound "Sb(III) complexed with Aldrich humic acid" (2.83 Å, Figure SI-8, Table SI-20), both reside in the range of published Sb−C distances of ∼2.85 -∼ 2.92 Å, 73,74 indicative for phenol groups.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Research has demonstrated that alkali metal ions cannot be removed by micro-organisms (Tobin et al 1984). By contrast, biosorbents have obvious adsorption efficiency for ions with high electronegativity (Feng et al 2013;Zhou et al 2019Zhou et al , 2021Lu et al 2021). For example, the maximum adsorption capacity of divalent metal ions is highly positively correlated with the radius of metal ions.…”
Section: Properties Of Metal Ionsmentioning
confidence: 99%
“…Compared with traditional heavy metals removal methods, EPS have many technological advantages, such as high recovery rate, biodegradability (Salehizadeh and Yan 2014) and a wonderful adsorption capacity for common metal ions (Feng et al 2013;Zhou et al 2019Zhou et al , 2021Lu et al 2021), because there are many types of surface functional groups (Liu and Fang 2002;Verstrepen and Klis 2006), which can provide adsorption sites for heavy metals ions. Hence, the biosorption of heavy metals has wide applications and provides new insights into removing low-concentration heavy metals pollutants in a water environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…hydroxyl, carboxyl, and amino) in MFX, which allow MFX to have good combining capacity with pollutants and have good flocculation efficiency [ 12 15 ]. In addition to the removal of turbidity of wastewater, it has been proved that MFX can treat wastewaters that contain heavy metals [ 16 18 ] and antibiotics [ 19 21 ]. Because there is no secondary pollution of MFX, it is one of the most promising materials to treat wastewater [ 22 ].…”
Section: Introductionmentioning
confidence: 99%